Local wisdom-based science e-module to improve cultural literacy and critical thinking skills of elementary school students - Wahyudi, Achmad Basari Eko; Salimi, Moh.; Hidayah, Ratna; Surya, Anesa; Suhartono, Suhartono; Wahyono, Wahyono (Education and Development Research, 2025)
The low critical thinking skills and cultural literacy of elementary school students, along with the absence of teaching materials that integrate local wisdom into science and social studies (IPAS) learning, present challenges that need to be addressed. This study aims to develop a local wisdom-based IPAS e-module to enhance students’ critical thinking skills and cultural literacy. The research employed the ADDIE development model, encompassing the stages of analysis, design, development, implementation, and evaluation, with feasibility tests conducted by material, media, and instructional experts. Practicality tests were carried out through one-to-one trials, small group trials, and field trials, while effectiveness tests applied a quasi-experimental design with control and experimental classes analyzed using pretest–posttest data and N-gain calculations. The results indicated that the e-module was rated “highly feasible” by all validators, with “highly practical” ratings from teachers and students. Effectiveness tests showed an improvement in critical thinking skills with an N-gain of 0.70 (high category) and an improvement in cultural literacy with an N-gain of 0.44 (medium category) in the experimental class, while the control class remained in the low category. This study concludes that the local wisdom-based IPAS e-module is effective as a learning resource for improving critical thinking skills and cultural literacy, while also serving as a medium for preserving regional culture in elementary schools.